The intersection of amyloid beta and tau in glutamatergic synaptic dysfunction and collapse in Alzheimer’s disease - Crimins, Johanna L. (2013)
The synaptic connections that form between neurons during development remain plastic and able to adapt throughout the lifespan, enabling learning and memory. However, during aging and in particular in neurodegenerative diseases, synapses become dysfunctional and degenerate, contributing to dementia. In the case of Alzheimer’s disease (AD), synapse loss is the strongest pathological correlate of cognitive decline, indicating that synaptic degeneration plays a central role in dementia. Over the past decade, strong evidence has emerged that oligomeric forms of amyloid beta, the protein that accumulates in senile plaques in the AD brain, contribute to degeneration of synaptic structure and function. More recent data indicate that pathological forms of tau protein, which accumulate in neurofibrillary tangles in the AD brain, also cause synaptic dysfunction and loss. In this review, we will present the case that soluble forms of both amyloid beta and tau protein act at the synapse to cause neural network dysfunction, and further that these two pathological proteins may act in concert to cause synaptic pathology. These data may have wide-ranging implications for the targeting of soluble pathological proteins in neurodegenerative diseases to prevent or reverse cognitive decline.